Momordica Charantia Polysaccharides Attenuates MPP+-Induced Injury in Parkinson’s Disease Mice and Cell Models by Regulating TLR4/MyD88/NF-κB Pathway - Dengjun Guo; Jie Zhou; Meng Zhang; Reyisha Taximaimaiti; Xiaoping Wang; Hai Wang (International Journal of Polymer Science)
Objective. To investigate the potential role of Momordica charantia polysaccharides (MCPs) in Parkinson’s disease (PD) and reveal the molecular mechanism of its function. Method. 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and 1-methyl-4-phenylpyridinium (1-methyl-4-phenylpyridinium, MPP+) were used to establish PD mice and cell models. The mice and cells were divided into 4 groups: Control group, Control+MCPs group, PD group, and PD+MCPs group. Pole climbing experiment and Rotarod experiment were used to observe the coordination ability of mice. High-performance liquid chromatography and enzyme-linked immunosorbent assay (ELISA) were used to determine neurotransmitters and metabolites, inflammatory factors TNF-α and IL-1β, oxidative stress-related markers SOD, MDA, and GSH in striatum tissues. Western blot was used to determine the protein levels of tyrosine hydroxylase (TH), oxidative stress-related protein Cytochrome C (Cytochrome C), and apoptosis-related proteins Bcl-2, Bax, and cleaved Caspase-3 in tissues and cells. Moreover, flow cytometry, PI staining, and fluorescence were used to observe cell apoptosis. Finally, the activation effect of MCPs on TLR4/MyD88/NF-κB signaling pathway was observed and verified. Results. Compared with the Control group, MPTP treatment can induce brain damage in mice (all P<0.05), change the metabolic state of neurotransmitters (all P<0.05), induce inflammation (all P<0.05), and induce apoptosis and the occurrence of oxidation reaction (all P<0.05); however, MCPs treatment can significantly reverse the above changes (all P<0.05). In cell models, studies have found that MCPs can play a protective role by regulating the activation state of TLR4/MyD88/NF-κB pathway. Conclusion. This study found that the application of MCPs therapy can play anti-inflammatory, antioxidative stress, and antiapoptotic effects in PD by regulating the activation of the TLR4/MyD88/NF-κB pathway.